THE EFFECTIVENESS OF TEACHING VOCABULARY USING PICTURES (ELang | An English Language Education Journal, 2021)
This title of this research paper are “The Effectiveness of Teaching Vocabulary Using Pictures”. This is to determine the effect of teaching vocabulary using pictures as a medium of learning English for junior high school students in the first grade. This is to find out how much influence the use of teaching vocabulary using pictures as a medium for learning English for junior high school students in the first grade. The population as a source of data in this study are 30 students, at the first grade student of SMP N 3 Ciwidey. The method used in this study is an experimental design method. The method for collecting data was administering pre–test and post–test. The instrument used in this study is vocabulary test. The researcher finds some conclusion. it showed that the t count = 4.173 was bigger than t table= 2.045 lied on the significant level 0.05 with the DF = 30. (Ha) that states there is significant difference of students’ vocabulary achievement by using pictures was accepted, while the Null Hypothesis (Ho) was reflected. This means that teaching English vocabulary using pictures to the first grade of SMPN 3 Ciwidey is effective.